The Comparison Analysis Of Rigid And Soft Rigid Material Custom Foot Orthosis On Flat Foot Reduction - Prasetyo Catur Utomo; Atika Febri Anggriani (Jurnal Keterapian Fisik, 2022)
Background: The most frequent musculoskeletal problems, with the passage of time, are flatfoot. According to research, approximately 20–30% of all children in the globe have flat feet, and there are approximately 129 (40%) children that have a flat foot propensity, as determined by the findings of an examination conducted in Sukajadi District, Bandung. Prosthetic orthotics can give medial arch support with sponge and plastic materials in the treatment of flat feet, with the goal of providing support to the plantar foot and restoring the arch form of the foot. Methods: This is a quasi-experimental study with only a two-group post-test design. This study compared two research groups: one with a rigid custom foot orthosis and one with a soft rigid custom foot orthosis.The total number of research samples is 26. Results: The results of the Wilcoxon hypothesis analysis show that using a rigid custom foot orthosis reduces the degree of flat foot by 0.002 and using a soft rigid custom foot orthosis reduces the degree of flat foot by 0.059. As a result, when comparing the use of a rigid custom foot orthosis to the use of a soft rigid custom foot orthosis with the same intervention time in both groups of research subjects. Conclusion: When compared to the use of a soft rigid custom foot orthosis with the same intervention period in both groups of research subjects, the use of a rigid custom foot orthosis is more able to minimize the degree of flat foot.